Perancangan Kecerdasan Buatan pada NPC Menggunakan UNITY 2D dan Perilakunya terhadap Player - Rahmad Danil Fajri; Muhammad Arvy Syahputra; Teuku Raja Muhammad Zaki; Aries Saifudin; Irpan Kusyadi (Teknik Informatika Universitas Pamulang, 2021)
The application of artificial intelligence (AI) in a video game is one of the many technological innovations. One variation of 2D-based and offline-based games often applies artificial intelligence to their products to make the games they make interesting. In developing this artificial intelligence, State Machine (SM) is considered very fitting in programming the NPCs used against enemies (Enemy) in the game so that they have variations in movement, attack ranges, and different interaction patterns for each enemy.